Comparison of Electrons and Photons Treatment Plans in Medulloblastoma Patients - Muhammad Usman Ghani; Aasia Razzaq; Nauman Amjad; Ismat Fatima (Indonesian Journal of Cancer, 2023)
Background: The treatment of medulloblastoma involves surgery, radiotherapy, and adjuvant chemotherapy. In radiotherapy, craniospinal irradiation (CSI) is prescribed, where two lateral cranial fields and one or two spinal beams are applied in CSI. Different multi-field techniques (coplanar and/or noncoplanar) are used to register the prescribed dose. The purpose of this study was to assess plan quality in terms of dose coverage of the spine with both photon and electron beam therapy and the sparing of organs at risks (OARs).Methods: Ten pediatric patients (ages 6 to 10 years) were immobilized in the prone position for simulation. The Clinical Target Volume (CTV) of the organ under treatment, Planning Target volume (PTV) of the organ under treatment, and OARs were contoured. Prowess Panther (v4.71) was used for dose computations. Two lateral parallel-opposed 6 MV photon cranial fields with the spinal beam(s) (either 6 Photons or 21 MeV electrons) were used in planning. Electron beams were added posteriorly on the spine with parallel-opposed cranial fields. The treatment plans were computed for 3600 c Gy in 21 fractions.Results: For comparable conformity number of electron versus photons beam plans (0.68 ± 0.41 versus 0.66 ± 0.47, is not significantly different at p < 0.05) and homogeneity index (1.22 ± 0.03 versus 1.25 ± 0.04, is significantly different at p < 0.05), the photon doses were higher for underlying OARs (heart, liver, and thyroid) and were lower for partially in-field organs (lungs and kidneys) compared to electrons.Conclusions: The underlying organs i.e., thyroid, heart, and liver receive a lesser dose in case of electrons, while partially in-field organs are exposed more compared to photons mainly due to the ballooning effect in electrons. The study shows that both electrons and photons can be used for CSI. However, the electron may be preferred due to its better sparing of underlying structures.